No Zero Sum Game Between the Evolving Role of the State and Market Forces in China - Knowledge@SMU (Institutional Knowledge at Singapore Management University, 2007)
Is China’s remarkable economic progress a success story of market forces triumphing over the state in lifting millions out of poverty? Singapore Management University political science professor John Donaldson presents the case that, even as China underwent market reforms and emerged with impressive results, the role of the state did not diminish but shifted to other vital tasks and functions to facilitate and alter market forces. He also argues that, in this country of over 1.3 billion people, economic growth alone does not necessarily lead to poverty reduction.